2021
DOI: 10.26509/frbc-ec-202113
|View full text |Cite
|
Sign up to set email alerts
|

How Well Did PPP Loans Reach Low- and Moderate-Income Communities?

Abstract: We investigate the degree to which Paycheck Protection Program (PPP) loans reached small businesses in low- and moderate-income (LMI) communities. We use PPP loan data from the Small Business Administration that we geocode and link to census tracts. We assess the program’s reach in a few ways and focus on the number of loans, rather than the amount of funds, that went to different areas in order to capture the program’s impact on businesses with fewer than 50 employees—the vast majority of small businesses. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…Counties with higher median income levels are positively related to the loan amount awarded in 2020, but negatively related in 2021 and when both years are considered (Table 3). The 2020 result aligns with Schweitzer and Borawski (2021) findings showing that PPP loans had a broad reach to low- and middle-income communities served by the CRA loans. In our case, however, we do not find loan demand, as proxied by CRA lending, to have a statistically significant effect.…”
Section: Results Of Macro-level Analysissupporting
confidence: 74%
“…Counties with higher median income levels are positively related to the loan amount awarded in 2020, but negatively related in 2021 and when both years are considered (Table 3). The 2020 result aligns with Schweitzer and Borawski (2021) findings showing that PPP loans had a broad reach to low- and middle-income communities served by the CRA loans. In our case, however, we do not find loan demand, as proxied by CRA lending, to have a statistically significant effect.…”
Section: Results Of Macro-level Analysissupporting
confidence: 74%
“…PPP loans in 2020 represented unprecedented support for small businesses-support that was not dependent on the creditworthiness of businesses-but we continued to see that minority-owned businesses were more likely to receive less funding than they applied for from the program. The PPP clearly reached a wide swath of small businesses, including low-and moderate-income communities (Schweitzer & Borawski, 2021), but our results confirm that differences in general credit results for minority businesses still spilled over into the program. Given that PPP loans involved very little risk for the lender, the differences we identify in PPP loan receipts seem to mostly reflect the challenges that minority-owned businesses face interacting with banks and other lenders.…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 48%
“…Despite the broad coverage of the program, analysis of the business addresses in the 2020 PPP lending files identified lower frequencies of PPP loans per capita in low-and moderate-income communities and for businesses located in census tracts with larger minority populations (Schweitzer & Borawski, 2021). Using the small fraction of PPP loans where the race of the owner was identified, Atkins et al (2022) showed that Black-owned firms received loans that were roughly half the size of White-owned firms.…”
Section: Lenders and The 2020 Pppmentioning
confidence: 99%
“…Despite the high degree of heterogeneity in the pandemic impact on businesses, the distribution of PPP loans is largely untargeted and prioritizes speedy loan disbursement (Autor et al, 2022). According to Autor et al (2020), initially about 70% of eligible firms applied for PPP loans, and Borawski and Schweitzer (2021) report that by the end of 2020 PPP loans had been taken up by 76% of U.S. small businesses. 3 It is not clear what the effect of targeting rescue policies to impacted firms is, and more generally, how effective small-business rescue policies are for macroeconomic outcomes.…”
Section: Covid-19 Pandemic In the Us And Rescue Policiesmentioning
confidence: 99%